« Famille en danger » : matérialités et fabrique des ayants-droit aux logements sociaux en Algérie - Laurence Dufresne Aubertin (L’Année du Maghreb)
In Algeria, the distribution of social housing refers to the population’s expectations towards the state in regards to providing forms of subsistence. This article focuses on the practices and representations of applicants for social housing living in buildings threatening to collapse, in basement and on terraces in impoverished neighborhoods in downtown Oran. Through the material demands for social housing, this article questions the political relations that are established through material mediation. By focusing on objects that materialize social grievances, it explores the ways in which applicants for social housing attempt to construct themselves as rights-holders and assert their right to access this resource in a situation of constraint. This article focuses on three types of material supports - namely precarious housing, documentary devices and banners - to analyze modalities of political subjectivation.